LOSS AND GAIN IN TRANSLATION PROCESS IN BIG NATE COMIC STRIPS BOOKS INTO INDONESIAN - Adi Utamayasa, I Gede; pastika, I Wayan; Sukarini, Ni Wayan (JOURNAL OF LANGUAGE AND TRANSLATION STUDIES, 2017)
ABSTRACTThe article entitled Loss and Gain in Translation Process In Big Nate Comic Strips Books Into Indonesian. The aim of the article is to analyze deeply about the kinds of structural loss and gain found in the comic. The observation done in this qualitative research utilized note-taking technique to find kind of loss and gain in the translation process of the comic. The next step is describing the kinds of loss and gain in the process of translation. The theory of kinds of losses and gain used to analyze the problems, to find kinds loss and gain in translation process of the comic (Basnett, 1991). As the result of the research, the researcher concluded that the translator sometimes lost or gained some words, phrases or even clauses to make the translation acceptable and readable to the target readers and to make it sounds more natural in the target language.ABSTRAKArtikel ini berjudul Loss and Gain in Translation Process In Big Nate Comic Strips Books Into Indonesian. Analisis artikel ini adalah tentang jenis penghilangan dan penambahan secara struktural yang ditemukan pada komik. Teknik pengamatan dalam metode penelitian kualitatif yang dilakukan dalam studi ini disertai dengan pencatatan untuk menemukan jenis penghilangan dan penambahan di dalam proses penerjemahan. Teori jenis penghilangan dan penambahan yang digunakan untuk menelaah masalah, untuk menemukan jenis penghilangan dan penambahan dalam proses penerjemahan komik (Basnett, 1991). Hasil penelitian menunjukkan bahwa penerjemah terkadang menghilangkan atau menambahkan kata, frase, atau bahkan klausa untuk membuat hasil terjemahan mudah diterima dan dibaca oleh pembaca serta terdengar lebih alami dalam bahasa target.